On Homogeneous Parameter-Dependent Quadratic Lyapunov Function for Robust H∞ Filtering Design in Switched Linear Discrete-Time Systems with Polytopic Uncertainties. (15th February 2015) - Pang, Guochen; Zhang, Kanjian
Abstract : This paper is concerned with the problem of robust H ∞ filter design for switched linear discrete-time systems with polytopic uncertainties. The condition of being robustly asymptotically stable for uncertain switched system and less conservative H ∞ noise-attenuation level bounds are obtained by homogeneous parameter-dependent quadratic Lyapunov function. Moreover, a more feasible and effective method against the variations of uncertain parameter robust switched linear filter is designed under the given arbitrary switching signal. Lastly, simulation results are used to illustrate the effectiveness of our method.